PENGARUH EFEKTIVITAS MODAL SENDIRI, LIKUIDITAS, DAN SOLVABILITAS TERHADAP TINGKAT RENTABILITAS PADA KOPERASI - Bagus Hariwangsa, I Putu Gede; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
The aim of a credit union is to improve the profitability of the cooperative. With the high rate of return that means the cooperative is already working efficiently. So both companies and cooperatives are not just trying to maximize profits but more important is the effort to heighten profitability. Factors that may affect the level of profitability is the effectiveness of its own capital, liquidity and solvency. This study aims to provide empirical evidence about the influence the effectiveness of their own capital, liquidity solvency of the level of profitability. The object of this study is that there are savings and credit cooperatives in Tabanan regency period 2011-2015. The data analysis technique used is multiple linear analysis. Hypothesis testing results show that the variable effectiveness of its own capital and solvency positive and significant impact on the level of profitability, while liquidity levels negatively affect the profitability level.
Keywords: The Effectiveness of Own Capital, Liquidity, Solvency, Liquidity and Profitability Level